Piano performance in a semiotic key: Society, musical canon and novel discourses - Navickaité-Martinelli, Lina (Finland Semiotic society of Finland, 2014)
In an attempt to expand and enrich the existing trends of musical performance studies, as well as exploit the potentials of semiotic analysis, this dissertation offers the theoretical perspective that enables the unfolding of the multiple meanings generated by and communicated through the performer's art. Without denying that musical performance is inevitably associated with the opus, the semiotic approach, it is proposed here, should study performance as encompassing all the exogenic meanings that do not necessarily depend on a musical work. Thus, the focus of the present dissertation is the figure of a classical music performer as a significant part of society, as well as cultural, institutional and personal discourses that both generate the art of music performance and originate from it. The main targets here are mapping the predominant tendencies of the art of musical performance during the twentieth century and proposing a form of semiotic analysis of different representations and self-representations that musical performers, pianists in particular, put into action in their interactions with social and cultural contexts (including different types of performer-listener communication processes, scholarly analyses, the various media through which the art of music performance is disseminated, and aspects related to the marketing and ideologizing of today s performance practices). The dissertation is structured into four parts. Part 1 introduces a semiotic framework for studying musical performance. Part 2 discusses a variety of meanings communicated through the performers art as well as the media in which the art of classical piano music performance is operating. Part 3 positions the performers art within the Western musical canon by examining Beethoven interpretations as played by pianists of various cultural and historical backgrounds. The concluding Part 4 presents novel discourses on the art of musical performance by analyzing 11 personal websites of Lithuanian classical pianists as an important vehicle of contemporary performers for communicating their artistic identities. It is claimed in this dissertation that the combination of semiotic and musicological approaches is relevant and revealing in the study of musical performance art in that it strongly make a case for current musicology to elaborate increasingly interdisciplinary paradigms and modes of investigation.